Bacterial translocation in colorectal cancer patients - Alina Ogizbayeva; Yermek Turgunov (Ķazaķstannyṇ Klinikalyķ Medicinasy, 2021)
Bacterial translocation is the penetration of intestinal bacteria through the intestinal mucosa into usually sterile tissues and internal organs. Commensal bacteria, despite their presence in the intestine in extremely large numbers, rarely cause local or systemic inflammation, because the unicellular epithelial layer of the intestinal mucosa prevents the migration of these bacteria from the intestine. For years, researchers have wondered how a single layer of intestinal epithelial cells can prevent microorganisms from entering the systemic circulation. Today, the phenomenon of bacterial translocation is considered as one of the main mechanisms of endotoxemia and systemic inflammatory response syndrome in various pathologies, including colorectal cancer and acute bowel obstruction. This narrative review is devoted to the search for factors promoting to bacterial translocation from the intestine in colorectal cancer and acute malignant bowel obstruction.